Application of concentrated growth factor to autotransplantation with inflammation in recipient area - Dilinuer Keranmu; Ailimaierdan Ainiwaer; Nijiati Nuermuhanmode; Wang Ling (BMC, 2021)
Abstract Objective The purpose of this study was to apply concentrated growth factor (CGF) to the transplanted area with inflammation, to observe the clinical effects of CGF on the inflammation area assisted by 3D printing technology. Methods A total of 52 compromised mandibular first or second molar with chronic periapical lesions were transplanted with mature third molars. The patients were divided into CGF group (n = 26) and control group (n = 26) and transplanted into fresh extraction sockets with or without CGF. All the patients underwent clinical and radiographic examinations during the follow-up. Results Average surgery and extra-oral time were 39 min (± 7.8) and 42 s (± 10.2). The success rates of CGF group and control group were 100% and 92.3% respectively. Most of the periapical lesions in CGF group healed completely within 3 months, which was significantly faster than control group. The initial stability of CGF group was better than control group immediately after operation, and the degree of pain in CGF group was lower than control group on the 1st and 3rd day after operation. Conclusions The application of CGF in recipient site with chronic periapical lesions can accelerate the regeneration of alveolar bone and the healing of inflammation, greatly shorten the healing period. Meanwhile, CGF help to reduce postoperative pain and reaction at the early stage of healing and increase the success rate of autogenous tooth transplantation (ATT). Additionally, the use of 3D printing model can greatly reduce the extra-oral time of donor teeth.